Efektifitas Metode Total Physical Response (TPR) dalam Meningkatkan Hasil Belajar Maharah Qiraah Santri Ula di Madrasah Diniyah Darut Taqwa Sengonagung Purwosari Pasuruan - Fauziyah Laili (CV. Satria Jaya, 2023)
Arabic language is one of the materials taught at Madrasah Diniah Darut Taqwa in terms of delivery, the teachers most use the caourse model which in this case does not so effective in achieving a learning goal. The goal of this learn was to specify the effectiveness of the learning method used in this study. Namely the Total Phycical Response (TPR) learning method in improving maharah qiraah skills, both oral reading or reading comprehension of grade 3 students at Madrasah Diniah Darut Taqwa. The approach used by the resesrchers in this learn is a quantitative approach to the classify of Pre-Experimental Desighs in the form of one group pretets-posttest on one sample. While the research instrument used to obtain data is observation, documentation, test (pretest-posttest) and non-test (effective-psychomotor). From the result of this learn, it was deduceed that learning with the TPR method has a fairly high significance. This is based on the result of the second test score (post-test) which experienced a percentage increase of 8,4%.